Indígenas e iconografia didática : a imagem dos índios nos manuais de história do Programa Nacional do Livro Didático (2011) - Monteiro, Diogo Francisco Cruz (2012)
This dissertation is intended to identify the manners of adaptation of the images of indigenous theme of the History textbooks evaluated and distributed by the Programa Nacional do Livro Didático (PNLD) , of the year 2011, to the terms of the Law 11.645/08, on the part of their authors and publishers. For doing that, we proceeded to the analysis of the allegories about the agency related to the Indian in the textbooks. For the selection of the books here analyzed, we followed the criterion of selection of the titles that have been more often chosen during the evaluation process and choice of the textbooks by the teachers and managers of state public schools in Aracaju city, starting from the Guide of the textbook of PNLD 2011. The impressions concerning the indigenous people in the textbooks are expressed from the united analysis of the contents of their images, subtitles and nuclear texts. Thus, we chose to work with images of several types that are objects of descriptions, comments and reviews made by authors, not only in the texts of the subtitles but also in the nuclear texts of the analyzed books. Therefore, by doing this research, we aim to have a better understanding, in the present context, of the forms of treatment of the indigenous theme through the images of the History textbooks of the PNLD 2011.